Willingness to share supply chain data in an ecosystem governed platform - An interview study - Dahlberg T.; Nokkala T. (Slovenia, 2022)
The exchange of business documents and technical product data between the partners of industrial ecosystems can be automated and integrated through digital supply chain (DSC) platforms. The advocates, managers and developers of DSC platforms need to solve several technical and social challenges during the implementation of such platforms. Operative level officers’ willingness to share business and technical product data with partner organisations’ officers is one of them. This article presents findings from the interviews of 25 sourcing and accounting experts in two industrial ecosystems jointly developing a DSC platform to be governed by industrial ecosystems. The interviewees considered schedule data shareable and detailed design drawings non-shareable. We discovered 12 factors increasing and 9 factors decreasing the willingness to share data. Our study contributes to platform and ecosystem research and offers practical advice to the developers and other stakeholders of the investigated DSC platform.
32nd Bled eConference: Humanizing Technology for a Sustainable Society